A pilot randomised controlled trial of a web-based implementation intervention to increase child intake of fruit and vegetables within childcare centres - Courtney Barnes (Pilot and Feasibility Studies, 2020)
Abstract Background As dietary behaviours developed during early childhood are known to track into adulthood, interventions that aim to improve child nutrition at a population level are recommended. Whilst early childhood education and care (ECEC) is a promising setting for interventions targeting children’s nutrition behaviours, previous interventions have largely used high intensity, face-to-face approaches, limiting their reach, implementation and potential impact at a population level. Web-based modalities represent a promising means of supporting the delivery of childcare-based interventions whilst overcoming challenges of previous approaches; however, the feasibility of using such modalities to support implementation is largely unknown. As such, this study sought to collect feasibility and pilot data to inform the design of a web-based intervention together with health promotion officer support within childcare centres. Child dietary intake will also be assessed to provide an estimate of the impact of the implementation intervention. Methods A superiority cluster randomised controlled trial with repeat cross-sectional data collection employing an effectiveness-implementation type-II hybrid design will be conducted with childcare centres within the Hunter New England region of New South Wales, Australia. Type-II hybrid designs provide the opportunity to assess intervention efficacy whilst piloting the feasibility of the implementation strategies. Centres allocated to the intervention group will receive access to a web-based program together with health promotion officer support to implement targeted healthy eating practices to improve child diet in care. A number of outcomes will be assessed to inform the feasibility to conduct a larger trial, including childcare centre and parent recruitment and consent rates for each component of data collection, uptake of the implementation strategies, acceptability of the intervention and implementation strategies, appropriateness of the implementation strategies and the contextual factors influencing implementation. Discussion This study will provide high-quality evidence regarding the potential feasibility of a web-based intervention and the impact of healthy eating practices on child diet in care. Web-based modalities provide a promising approach for population-wide implementation support to childcare centres given their potential reach and consistency with existing infrastructure. Trial registration Prospectively registered with Australian New Zealand Clinical Trial Registry ( ACTRN12619001158156 ).